Increased p63 Expression in Canine Perianal Gland Tumours - Kim, Soo-Hyeon (J Vet Res, 2018)
INTRODUCTION: p63 is a homologous molecule of p53 and was recently identified as playing important roles in several key cellular processes, including epithelial development and proliferation. Since then, several studies have demonstrated altered p63 expression in various cancers of epithelial origin. Canine perianal gland tumour is one of the most common skin neoplasms in dogs; however, the molecular characteristics of this tumour remain poorly understood. The objective of the present study was to analyse and compare the expression of p63 in canine perianal gland adenomas and carcinomas. MATERIAL AND METHODS: Haematoxylin and eosin-stained slides were examined and immunohistochemistry was conducted for a total of 65 samples. Immunohistochemical data for p63 expressions were compared between groups using the Mann-Whitney U test. RESULTS: The p63 expression level was increased in perianal gland carcinomas compared to that in the adenoma samples (P < 0.0001). The percentage of cells expressing p63 was higher in perianal gland carcinomas than in adenomas, although the intensity of immunostaining did not differ significantly between the two groups. CONCLUSION: p63 is a candidate factor contributing to the malignant transformation and progression of canine perianal gland tumours.